Prevalence of stress and its associated factors among medical students in Sabah Malaysia Borneo - Aldrin Musiun; Khamisah Awang Lukman; Mohammad Saffree Jeffree; Fredie Robinson; Mohd Rohaizat Hassan; Hasanain Faisal Ghazi; Al-abed Ali Ahmed Al-abed; Naing Oo Tha; Swe; Shamsul Bahari Shamsudin (2019)
Stress is accepted as the accumulation of unpleasant state of physical, mental and emotion on a person. Medical education has been known as one of the most stressful academic curriculum. Hence, medical students may subjected to multiple psychological changes and challenges throughout the years of medical education. The aim of this study was to determine the prevalence of stress and its associated factors among medical students. This cross sectional study was conducted from April to May 2018 in medical school in Sabah. It involved 396 medical students through universal sampling. Self-administered questionnaires were used as an instrument for data collection. The questionnaires included were Sociodemographic Questionnaire, Depression, Anxiety and Stress Scales 21 (DASS-21) and Medical Student Stressors Questionnaire (MSSQ). Bivariate analysis (Chi Square test, Fisher’s Exact Test, Independent T test and Man-Whitney U test) were used to analyse the association. The response rate was 90.2%. The prevalence of stress among medical students were 33.3%. Significant associated factors include financial support inadequacy (p=0.010) and all categories of medical student stressors. The mean score of the academic related stressors was found to be at 2.117 (±0.758) which was the highest mean score among medical student stressors assessed by MSSQ. The result of this study can be used as a basis for implementation of preventive measures such as provision of comprehensive, integrated and responsive mental health care services in university-based settings.